1997
DOI: 10.1016/s0006-3495(97)78110-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in steady-state inactivation between Na channel isoforms affect local anesthetic binding affinity

Abstract: Cocaine and lidocaine are local anesthetics (LAs) that block Na currents in excitable tissues. Cocaine is also a cardiotoxic agent and can induce cardiac arrhythmia and ventricular fibrillation. Lidocaine is commonly used as a postinfarction antiarrhythmic agent. These LAs exert clinically relevant effects at concentrations that do not obviously affect the normal function of either nerve or skeletal muscle. We compared the cocaine and lidocaine affinities of human cardiac (hH1) and rat skeletal (mu 1) muscle N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 27 publications
7
75
0
Order By: Relevance
“…In particular, cardiac Na ϩ channels activate at a greater number of negative membrane potentials and are more sensitive to local anesthetics than are their skeletal muscle and nerve counterparts (Nuss et al, 1995;Wang et al, 1996;Wright et al, 1997). Clinically, 5 to 20 M lidocaine alters cardiac conduction by blocking Na ϩ channels, whereas Ͼ100 M is required to produce local anesthesia in nerve and skeletal muscle (Gianelly et al, 1967;Jewitt et al, 1968;Hille, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, cardiac Na ϩ channels activate at a greater number of negative membrane potentials and are more sensitive to local anesthetics than are their skeletal muscle and nerve counterparts (Nuss et al, 1995;Wang et al, 1996;Wright et al, 1997). Clinically, 5 to 20 M lidocaine alters cardiac conduction by blocking Na ϩ channels, whereas Ͼ100 M is required to produce local anesthesia in nerve and skeletal muscle (Gianelly et al, 1967;Jewitt et al, 1968;Hille, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, 5 to 20 M lidocaine alters cardiac conduction by blocking Na ϩ channels, whereas Ͼ100 M is required to produce local anesthesia in nerve and skeletal muscle (Gianelly et al, 1967;Jewitt et al, 1968;Hille, 1978). Despite advances in our understanding of the general mechanisms of LA block of Na ϩ channels, it remains controversial whether the enhanced drug sensitivity of the cardiac channels results from gating differences (Wright et al, 1997) or from an intrinsic difference in drug affinity (Nuss et al, 1995;Wang et al, 1996). In any case, the structural basis of isoform-specific differences in gating and drug sensitivity is poorly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Consequently, we compared lidocaine-induced UDB in the background of the cardiac isoform between the wild-type that has known QX access and mutants containing a single residue substitution in the D4 P-loop and D4S6 that should reduce access. In addition, we studied the reverse mutations in the skeletal muscle isoform for comparison with prior QX studies.…”
Section: Gating Kineticsmentioning
confidence: 99%
“…The increase in the fraction of inactivated with respect to resting channels on membrane depolarization, the so-called steady-state voltagedependence of inactivation, differs strongly between sodium channel isoforms from different tissues and between normal and mutant sodium channels. It has previously been shown that differences in the voltage-dependence of channel inactivation account for differences in sensitivity to sodium channel blocking agents with different binding affinities to resting with respect to inactivated channels between mutant and normal channels [18,50] and between sodium channel isoforms from different tissues [51,52]. Thus, mutant as well as sodium channels damaged by hypoxia, may increase sensitivity to a blocking drug by changing the voltage-dependence of channel inactivation [18,53].…”
mentioning
confidence: 99%